1995
DOI: 10.1136/ip.1.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes to and use of baby walkers in Dublin.

Abstract: Objectives-To identify the rate of baby walker use, parental attitudes, and associated injuries. Design-Parents of babies attending clinics for developmental assessment were surveyed by self administered questionnaire about their use, attitudes, and history of injuries associated with walkers. Setting-Dublin, Ireland. Subjects-Parents of 158 babies. Results-Fifty five per cent of the sample used a walker. The main reasons for doing so included babies' enjoyment of them and the fact that the walker was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 9 publications
3
19
1
1
Order By: Relevance
“…This was similar to the findings of a study in the United States [15]. Studies in the United Kingdom and Dublin showed that the rate of the use of walker was around 50% [9,21]. Some caregivers used walkers because they felt that walkers were good for their infants [9].…”
Section: Discussionsupporting
confidence: 85%
“…This was similar to the findings of a study in the United States [15]. Studies in the United Kingdom and Dublin showed that the rate of the use of walker was around 50% [9,21]. Some caregivers used walkers because they felt that walkers were good for their infants [9].…”
Section: Discussionsupporting
confidence: 85%
“…One third of parents in one study used walkers because they believed that walkers would keep their infants safe 10,11 . The majority of parents perceived the walker as being beneficial 12 . Bar‐on et al reported that 78% of the caregivers believed that the walker was beneficial and believed that walker use accelerated development of independent walking 4 …”
Section: Discussionmentioning
confidence: 99%
“…2001) and 77% (Bar‐on et al. 1998) of families had used a walker with their children in the United States of America (USA), 50% in Nottingham, United Kingdom (UK) (Kendrick & Marsh 1998), 55% in Dublin, Ireland (Laffoy et al. 1995) and 90% in Singapore (Thein et al.…”
Section: Introductionmentioning
confidence: 99%
“…A baby walker is a seat supported in a frame that has wheels, and surveys from several countries indicate their use is common. Those published from 1995 onwards indicate that between 46% (DiLillo et al 2001) and 77% (Bar-on et al 1998) of families had used a walker with their children in the United States of America (USA), 50% in Nottingham, United Kingdom (UK) (Kendrick & Marsh 1998), 55% in Dublin, Ireland (Laffoy et al 1995) and 90% in Singapore (Thein et al 1997). Walker-associated accidents are common, having been reported by 12-50% of parents using them (Kavanagh & Banco 1982, Stoffman et al 1984, Mayr et al 1994, Laffoy et al 1995, Thein et al 1997.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation